2017
DOI: 10.1002/masy.201600129
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Stability and Cytotoxicity of Precursor Microemulsions to Prepare Core‐Shell Polymeric Nanoparticles for Pharmaceutical Applications

Abstract: The preparation of biocompatible normal (oil‐in‐water, o/w) microemulsions (ME) with different oil phases (peppermint oil, trans‐anethole, vitamin E, jojoba oil) and stabilized with d‐α polyethylene glycol succinate (TPGS‐1000) and isobutanol (iso‐BuOH) is presented. Results of average particle diameter determination, Dp, indicated 6.35 ≤ Dp ≤ 10.24 nm. These ME showed excellent colloidal stability (−40 and +40 °C) and, without any drug loaded, decreased dramatically the viability of leukemia cells (K562), 60–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[5,6] To reduce the number of animals used, appropriate in vitro investigations can be used for screening prospective materials for estimations of toxic effects. [7,8] Cytotoxicity in vitro assay is the first test to evaluate the biocompatibility of any material used in biomedical devices. However, these tests have a great number of limitations and cannot mimic the biological environment.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] To reduce the number of animals used, appropriate in vitro investigations can be used for screening prospective materials for estimations of toxic effects. [7,8] Cytotoxicity in vitro assay is the first test to evaluate the biocompatibility of any material used in biomedical devices. However, these tests have a great number of limitations and cannot mimic the biological environment.…”
Section: Introductionmentioning
confidence: 99%
“…PACL has low water solubility and thus is formulated into organic solvents such as polyoxyethylated castor oil/dehydrated ethanol (50/50), but such organic solvents cause side effects such as hypersensitivity reactions . To avoid the use of such organic solvents, essential oils or other plant based oils can be used to dissolve the chemotherapeutic drug, as in previous works of other researchers, , and then attached to the biobased NPs, during their formation using the solvent/antisolvent method. In addition, it has been shown that the addition of essential oils and anticancer drugs can lead to synergistic effects and minimize the side effects …”
Section: Introductionmentioning
confidence: 99%